HUBUNGAN ANTARA THE BIG FIVE PERSONALITY TRAITS DENGAN FEAR OF MISSING OUT ABOUT SOCIAL MEDIA PADA MAHASISWA - Tresnawati, Febrina Rani (Intuisi : Jurnal Psikologi Ilmiah, 2016)
Abstrak.Â Keinginan untuk selalu mengetahui update pada media sosial dapat menyebabkan individu memiliki ketakutan untuk selalu ingin melihat update di media sosial. Ketakutan ini dapat terjadi pada siapa saja termasuk pada mahasiswa sebagai pengguna aktif media sosial. Ketakutan yang dirasakan setiap individu dapat berbeda. Perbedaan individu salah satunya dapat diihat dari trait kepribadian. Salah satu teori trait kepribadian adalah the big five personality traits, yakni openness, conscientiousness, extraversion, agreeableness, neuroticism. Penelitian ini bertujuan untuk mengetahui hubungan antara the big five personality traits dengan fear of missing out about social media. Penelitian ini merupakan penelitian kuantitatif korelasional. Sampel penelitian berjumlah 643 mahasiswa dengan menggunakan multistage cluster sampling. Data penelitian the big five personality traits diambil menggunakan skala Big Five Inventory. Variabel kedua diukur dengan skala fear of missing out about social media. Hasil analisis ini menghasilkan koefisien korelasi secara stimultan dengan r= 0,248 dan signifikansi atau p = 0,000, sehingga hipotesis yang menyatakan ada hubungan antara the big five personality traits dengan fear of missing out about social media diterima. Hasil penelitian menunjukkan trait kepribadian yang memiliki korelasi positif dengan fear of missing out about social media yaitu extraversion dan agreeableness. Sedangkan neuroticism berkorelasi negatif, conscientiousness tidak berkorelasi dan openness dinyatakan tidak liniear sehingga tidak dilakukan uji hipotesis.Abstract.Â The longing to always knowing the update in social media causes each individual has fear for always knowing their friendâs update in social media. This fear could raise to anyone including students as the active users of social media. The fear that raises each of individual may differ from one another. One of them is individual differencess that can be seen from personality trait. One of the personality trait theory is the big five personality traits, which are openness, conscientiousness, extraversion, agreeableness, neuroticism. The purpose of this research is to know the relationship between the big five personality traits and fear of missing out about social media.This research is quantitative correlation research. The samples of this research are 643 students by using multistage cluster sampling. The data of the big five personality traits is taken using adapted Big Five Inventory scale totaling 44 items. The second variable measure by The fear of missing out about social media scale is modification from previous research which has 19 items. The analysis is resulting r= 0,248 with significance or p = 0,000, so that hypothesis which claims the relationship between the big five personality traits and fear of missing out about social media is accepted. The result shows personality trait that has positif correlation with fear of missing out about social media is extraversion and agreeableness. Meanwhile, neuroticism is negatively correlated, conscientiousness is not correlated and openness personality trait is claimed not linear so no hypothesis test needed. The recommendation which could be given is that we should use social media wisely because the more time spent on surfing, especially in social media could make the user feels the fear of missing the updates in social media and it could grows into internet addiction.